Evidence for ACTN3 as a speed gene in isolated human muscle fibers - Broos, S.; Malisoux, L.; Theisen, D.; van Thienen, R.; Ramaekers, M.; Jamart, C.; Deldicque, L.; Thomis, M. A.; Francaux , M. (PLOS ONE, 2016)
Purpose: To examine the effect of a-actinin-3 deficiency due to homozygosity for the ACTN3 577X-allele on contractile and morphological properties of fast muscle fibers in non-athletic young men.